ANALISIS MODEL PEMBELAJARAN YURISPRUDENSI DENGAN STRATEGI DEBAT DALAM MEMBANGUN KEMAMPUAN ARGUMENTATIF SISWA - Amanda, Restu Rizki; Syahidin, Syahidin; Nazhan, Faiz Aswa; Muzakki, Rifqi Fathan Saepudin (Universitas Islam Negeri Alauddin Makassar, 2024)
Critical and argumentative thinking skills are essential for students, especially in understanding and applying religious knowledge. In practice, however, teaching in many educational institutions still predominantly uses one-way or lecture-based learning models. This approach often leads to students being passive and less engaged in critical thinking processes, such as analyzing, evaluating, and constructing arguments based on facts and logic. As a result, students’ ability to build sound arguments and defend their opinions scientifically tends to be weak. This research aims to explore the development of effective learning models to enhance students' argumentative skills. Through this study, it is hoped that relevant and practical teaching strategies can be identified to optimize students' argumentative abilities, thereby creating a learning environment that supports the improvement of critical and analytical thinking skills. The research employs a qualitative approach with a literature review method for data collection. This approach seeks to examine various references and prior studies to identify effective learning models and strategies for developing students' argumentative skills. The findings of this research indicate that the jurisprudential learning model combined with a debate strategy can be an effective option for improving students' critical thinking and argumentative abilities. Through a structured debate process, students are not only encouraged to understand fundamental jurisprudential concepts but also become skilled in constructing logical arguments, confidently presenting their opinions, and responding to opposing views constructively. Therefore, this model is worth considering as an approach to fostering higher-order thinking skills among students.